Physical, chemical, bacteriological and radioisotopic parameters from springs and wells around Jocotitlan volcano, Mexico. (3rd March 2006) - Gomez, Araceli Baca; Segovia, N.; Miranda, Veronica Martinez; Armienta, M.A.; Reyes, Rosa; Garcia, Jose; Munoz, Beatriz; Seidel, J.L.
Samples from seven springs and two wells around Jocotitlan volcano (Mexico), mainly used as drinking water supplies, were studied for physical, chemical, bacteriological and radioisotopic parameters. The temperature of the majority of the water was 5°C higher than the average atmospheric temperature of the zone, indicating a geothermal potential. The water type was bicarbonated mixed, related to magmatic CO2 absorption, and showed a dilution factor from meteoric waters. Calculations of the geothermal reservoir temperature indicate a potential use for direct rural and industrial applications. Trace elements, including radon and radium, were within the drinking water standards. Four springs showed bacteriological contamination due to cattle access and domestic waste pollution.